2022
DOI: 10.36469/001c.37307
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Comorbidities, Psychiatric Disorders, Healthcare Resource Utilization and Costs Among Adults with Essential Tremor: A Retrospective Observational Study in a Large US Commercially Insured and Medicare Advantage Population

Abstract: Background: Essential tremor (ET), the most common movement disorder, often impairs patients’ ability to perform activities of daily living, mental health, and quality of life. Objectives: To assess comorbidities, psychiatric disorders, healthcare resource utilization (HCRU), and costs among patients with ET compared with patients without ET. Methods: This retrospective observational study was conducted using a large US administrative claims database. Patients with ET were identified during the study period (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…Therefore, we may have underestimated the prevalence of multimorbidity, anxiety, and depression in the study. 32 , 55 Since identification of all comorbid conditions was based on ICD-10-CM codes only, coding errors and misclassification were likely. However, this approach is conventionally used in many observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we may have underestimated the prevalence of multimorbidity, anxiety, and depression in the study. 32 , 55 Since identification of all comorbid conditions was based on ICD-10-CM codes only, coding errors and misclassification were likely. However, this approach is conventionally used in many observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of more than 5 million US veterans, patients with ET were more likely than those without ET to have numerous comorbidities. 2 Patients with ET were, in fact, more likely to have many of the comorbidities reported by Dai et al, 1 including hypertension, obesity, hyperlipidemia, diabetes mellitus, ischemic heart disease, and inflammatory bowel disease. 2 In the veteran study, post-traumatic stress disorder, anxiety, and depression were the most common psychiatric diagnoses in ET patients, with the odds ratio exceeding 2.…”
mentioning
confidence: 92%
“…read with great interest the article by Dai et al 1 and was intrigued by data that demonstrated significant increases in the prevalence of numerous medical comorbidities in patients with essential tremor (ET). The authors reported that patients with ET had a higher number of comorbidities than non-ET patients (5.3 [3.2] vs 4.0 [3.3]).…”
mentioning
confidence: 99%
See 2 more Smart Citations